2009
DOI: 10.1186/1756-0500-2-78
|View full text |Cite
|
Sign up to set email alerts
|

Association of a single nucleotide polymorphism in titin gene with marbling in Japanese Black beef cattle

Abstract: BackgroundMarbling defined by the amount and distribution of intramuscular fat is an economically important trait of beef cattle in Japan. We have recently reported that single nucleotide polymorphisms (SNPs) in the endothelial differentiation, sphingolipid G-protein-coupled receptor, 1 (EDG1) gene were associated with marbling in Japanese Black beef cattle. As well as EDG1, the titin (TTN) gene, involved in myofibrillogenesis, has been previously shown to possess expression difference in musculus longissimus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 23 publications
3
30
1
1
Order By: Relevance
“…The TTN gene plays a role in myofibrillogenesis and is associated with marbling [22]. Moreover, the 231054C>T variant within the promoter region of TTN is associated with a marbling trait and is differentially expressed between high- and low-marbling muscle samples [23]. However, many NS/SS/Is likely affect the function of titin, which acts as a molecular spring for the passive elasticity of muscles [24].…”
Section: Resultsmentioning
confidence: 99%
“…The TTN gene plays a role in myofibrillogenesis and is associated with marbling [22]. Moreover, the 231054C>T variant within the promoter region of TTN is associated with a marbling trait and is differentially expressed between high- and low-marbling muscle samples [23]. However, many NS/SS/Is likely affect the function of titin, which acts as a molecular spring for the passive elasticity of muscles [24].…”
Section: Resultsmentioning
confidence: 99%
“…; Yamada et al . ,,,). These findings suggested that single nucleotide polymorphisms (SNPs) associated with BMS on these genes would be useful for effective marker‐assisted selection to increase marbling levels in Japanese Black cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphisms in other genes e.g. MYPN, MHC, TTN have been correlated with water holding capacity, tenderness and marbling but not commercialised (Grzes et al, 2007;Jiao, Zan, Liu, Wang, & Guo, 2010;Yamada et al, 2009). There is thus a gap in knowledge and a need for further research on muscle-related genes that may be relevant for meat quality.…”
Section: Introductionmentioning
confidence: 94%